Removal of Sulfur Kerosene Oil by Adsorption on Plastic Clay - Jaiswal, Mona (Asian Journal of Chemistry, 2010)
The removal of mercaptan sulfur from kerosene-oil by adsorption on plastic clay at different temperatures has been studied. The extent of adsorption of sulfur from kerosene-oil on plastic clay increases from 87.0 to 94.0% with the increase of temperature from 303 to 323 K respectively. The Langmuir isotherm can be used to represent the equilibrium data at various temperatures. The process of adsorption is endothermic.